2018
DOI: 10.1016/j.jcct.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A four-tier classification system of pulmonary artery metrics on computed tomography for the diagnosis and prognosis of pulmonary hypertension

Abstract: A CT-based four-tier severity classification system of PA diameter and its ratio to the aortic diameter has high accuracy for PH diagnosis with increased mortality in patients with moderate-severe severity grades. These results may support clinical utilization on chest and cardiac CT reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
(31 reference statements)
2
34
2
1
Order By: Relevance
“…In the current study, patients who died of RHF tended to have a higher frequency of exclusively chronic peripheral PE and a greater mean dRV/dLV ratio on presenting CT scans compared with survivors. As opposed to the results reported by Truong et al [ 33 ], we found no significant associations of baseline dPA and dPA/dAA ratio with mortality. However, when comparing the current study with the study by Truong et al [ 33 ], one must consider the differences in study design and study population between the two investigations: The patient cohort evaluated by Truong et al [ 33 ] was heterogeneous, consisting of 92 non-PH patients and 136 PH patients; during a median follow-up of 6.4 years (5.0–8.2 years) there were 85 deaths, 65 in the PH group and 20 in the non-PH group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, patients who died of RHF tended to have a higher frequency of exclusively chronic peripheral PE and a greater mean dRV/dLV ratio on presenting CT scans compared with survivors. As opposed to the results reported by Truong et al [ 33 ], we found no significant associations of baseline dPA and dPA/dAA ratio with mortality. However, when comparing the current study with the study by Truong et al [ 33 ], one must consider the differences in study design and study population between the two investigations: The patient cohort evaluated by Truong et al [ 33 ] was heterogeneous, consisting of 92 non-PH patients and 136 PH patients; during a median follow-up of 6.4 years (5.0–8.2 years) there were 85 deaths, 65 in the PH group and 20 in the non-PH group.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study including 145 patients with CTEPH, Leone et al [ 4 ] demonstrated significant correlation of mPAP with dPA (p < 0.001) as well as significant associations of mPAP and PVR with severity of mosaic perfusion subclassified into three grades based on a visual scoring system. More recently, Truong et al [ 33 ] reported significant correlation of dPA and dPA/dAA ratio with mPAP and right atrial pressure, using a four-tier severity grading system. Moderate (≥ 31–34 mm) and severe (> 34mm) enlargement of the dPA, and moderate (> 1.0–1.1) and severe (> 1.1) increase of the dPA/dAA ratio were associated with increased mortality as compared to the dPA and dPA/dAA metrics classified as normal [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, [6] reported the diameter of AA as significantly higher in males than in females but our study showed no significant difference. [6,14,23] The results of our study revealed that diameters of RMB and LMB were higher than in previous studies. [11,24] These diameters were found higher in male, in both our study and in earlier studies.…”
Section: Min-max (Cm)contrasting
confidence: 62%
“…A wide range of cut-off values for identifying RHC-confirmed pulmonary hypertension have been proposed for MPAD (from 25 to 38 mm) and PA:Ao (from 0.84 to 1.4) [4,6,7,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. We elected to use the cut-offs proposed in the European Society of Cardiology/European Respiratory Society pulmonary hypertension guideline for our main analyses [13,14], but also ran analyses using a range of values, and found that alternative cut-off values performed better.…”
Section: Discussionmentioning
confidence: 99%